Orthogonal relation between wavefield polarization and fast S wave direction in the Val d'Agri region: An integrating method to investigate rock anisotropy. Issue 1 (15th January 2014) - Pischiutta, M.; Pastori, M.; Improta, L.; Salvini, F.; Rovelli, A.
Abstract [1] Wavefield polarization is investigated using 200 seismograms recorded by a network of 20 stations installed on rock outcrops in the Val d'Agri region that hosts the largest oil fields in the southern Apennines (Italy). Polarization is assessed both in the frequency and time domains through the individual‐station horizontal‐to‐vertical spectral ratio and covariance‐matrix analysis, respectively. We find that most of the stations show a persistent horizontal polarization of waveforms, with a NE‐SW predominant trend. This direction is orthogonal to the general trend of Quaternary normal faults in the region and to the maximum horizontal stress related to the present extensional regime. According to previous studies in other areas, such a directional effect is interpreted as due to the presence of fault‐related fracture fields, polarization being orthogonal to their predominant direction. A comparison with S wave anisotropy inferred from shear wave splitting indicates an orthogonal relation between horizontal polarization and fast S wave direction. This suggests that wavefield polarization and fast velocity direction are effects of the same cause: The existence of an anisotropic medium represented by fractured rocks where shear wave velocity is larger in the crack‐parallel component and compliance is larger perpendicularly to the crack strike. The latter is responsible for the observed anisotropic pattern of amplitudes of horizontal ground motion in the study area.